Options of socio-economic system for African societies - Okwuosa, Emanuel A. (Zaria, Nigeria : Ahmadu Bello University Press, 1994)
This book is about economic Development and factors that are responsible for the development and sustainment of capitalism and socialism
Includes bibliographical references (p. 221-230).
oo 16/07/2018
Loans
Keywords: Economics; Economic development; Africa